Effective Leadership and Infrastructural Development in Rivers State - N, Anyanwu Kingsley (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
This study has extensively investigated leadership and infrastructural development in Rivers state. The objectives of the study, research questions as well as the hypotheses were formulated and tested. The data for the research was generated basically from the primary source. The questionnaire was the major instrument used to generate the data. The study determined the sample size from the population of the study. The determined sample size was tested based on the questions posed to respondents. The statistical analysis that was adopted is the chi-square statistical technique while the simple percentage was used to test the questionnaires, the chi-square was used to test the formulated hypotheses. The findings show that there is significance relationship between leadership discipline and infrastructural development. Also that leadership integrity has impact on infrastructural development.